Development of Problem-Based Learning (PBL) Oriented E-Module to Improve Critical Thinking Skills for Elementary School Students - Ardiyanto, Eka Yudha; Suryani, Nunuk; Rahayu, Ucu (Jurnal Pendidikan Matematika, 2025)
The purpose of this study is to analyze the development procedure, validity and effectiveness of PBL-oriented e-module to improve critical thinking skills in fractional calculation operation materials for grade V elementary school students. The type of research method carried out is research and development (R&D) with its development procedure, namely ADDIE, and data collection techniques in the form of teacher and student observation sheets, questionnaires for the validation of material experts, media and learning, teacher and student response questionnaires, and knowledge tests. The results of this study are: (1) the procedure for developing PBL-oriented e-modules using the ADDIE stage, (2) the results of the assessment by material, media and learning experts stated that PBL-oriented e-modules are in the category of Good or Suitable for use with an average percentage of 77.7%, (3) PBL-oriented e-modules are effective in improving the critical thinking skills of grade V elementary school students. It can be seen from the average score of students' critical thinking skills between pretest and posttest as well as the experimental group with the control group according to the target, there is a significant difference (0.000 < 0.05